(untitled) (El Hilo de la Fabula, 2015)
Queer spaces are not physical places but areas of probabilities within a social space open to tolerance for the different and the ambiguous. Such spaces promote dynamics of visibility and integration that, according to Laurent Berlant and Michael Warner, foster alternative possibilities of identities, intelligibilities, publics, cultures, and sexualities challenging the privilege of heteronormativity in sexual culture. Starting with a brief history of the LGBTQ (Lesbian, Gay, Bisexual, Transsexual, Queer) movements, theoretically framed by, among others, Lacanian constructions of subjectivity, Michel Foucault’s conceptualization on biopower, and Judith Butler’s arguments on performativity and identity, this address maps the queer agency as a space of transcultural resistance. Finally, it concentrates on long-existing queer constructions and representations, though invisible or camouflaged, in contrast with new and recent paradigms and emphasizes the importance of visibility and integration into different communal spaces.